Partial object doubling in the periphery induced by negative afterimages - Ian M. Thornton; Anna Riga (i-Perception)
We describe a new phenomenon—partial object doubling—in which the perceived contours of peripherally viewed moving targets become distorted and duplicated. The effect appears to arise due to interactions between physically drawn contours and the strong negative afterimages that are dynamically released during stable viewing of the displays. An online demo is provided where the effect can be experienced and relevant parameters manipulated.